Pengembangan Multimedia Interaktif Berbasis Macromedia Flash 8 pada Pembelajaran Ilmu Pengetahuan Alam Kelas V Sekolah Dasar - Agna Bella Amanda; Bagus Amirul Mukmin; Kharisma Eka Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research is motivated by the results of observations and experiences of researchers, that the level of student learning is low as much as 48.38% of students get scores below the KKM. In the analysis of student needs, there is still a lack of IT-based learning media in Macromedia Flash 8 for Mrican 2 Elementary School students. As many as 96% of students prefer learning materials using sound, animation and quizzes. The problems include how is the development process, how is the validity, how is the practicality, how is the effectiveness of interactive multimedia based on Macromedia Flash 8 in learning science in grade V elementary schools. The purpose of this research is to develop Interactive Multimedia Based on Macromedia Flash 8 in Class V Elementary School Science Learning. This study uses research and development R&D methods with the ADDIE model. The conclusions of the results of this study are (1) The process of developing Interactive Multimedia using the ADDIE model goes through the stages of analysis, planning or design, development, implementation, evaluation stage. (2) The validity of the validator obtains an average validation result of 90.5%. (3) The practicality of the teacher's and students' responses obtained an average practicality result of 90.15%. (4) The effectiveness is obtained from classical completeness with a percentage of 88%. This learning media can be said to be valid, practical, and effective so that it is suitable for use in learning.